1995
DOI: 10.1016/0014-5793(95)00185-c
|View full text |Cite
|
Sign up to set email alerts
|

Differential codon usage: a safeguard against inappropriate expression of specialized genes?

Abstract: Recent work has suggested that rare codons are sometimes used for the regulation of specialized gene expression in bacteria. Moreover, the cellular levels of certain tRNAs may fluctuate with growth conditions. Evidence implicating such mechanisms in the control of photosynthesis in Rhodobacter, solventogenesis in Clostridium, sporulation in Streptomyces, and fimbrial phase variation in E. coli is summarized. It is suggested that such mechanisms will prove applicable to the control of numerous additional specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 43 publications
2
37
0
Order By: Relevance
“…The free energies of stabilization of the four terminators at the 3h end are all very similar, therefore excluding the hypothesis that the differential stability is caused by differences in hairpins, which are supposed to prevent exonucleases from degrading the coding sequence of the mRNA (Higgins et al, 1993). Finally, the reasons for the low stability of amyE and sacC transcripts could lie in the translation mechanism adapted to a particular growth phase (Saier, 1995), hence the features of the translation machinery of the exponential phase did not fit well with these transcripts. The double exponential decay of amyE mRNA in addition to the monophasic decay of the corresponding functional mRNA suggests that this mRNA exists in two different states in the cells : one state with a very short half-life, probably either unprotected or only poorly protected by ribosomes, and therefore highly sensitive to endonucleolytic attack, and the other ribosome-bound with a half-life within the same range as that of sacB and csn transcripts.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The free energies of stabilization of the four terminators at the 3h end are all very similar, therefore excluding the hypothesis that the differential stability is caused by differences in hairpins, which are supposed to prevent exonucleases from degrading the coding sequence of the mRNA (Higgins et al, 1993). Finally, the reasons for the low stability of amyE and sacC transcripts could lie in the translation mechanism adapted to a particular growth phase (Saier, 1995), hence the features of the translation machinery of the exponential phase did not fit well with these transcripts. The double exponential decay of amyE mRNA in addition to the monophasic decay of the corresponding functional mRNA suggests that this mRNA exists in two different states in the cells : one state with a very short half-life, probably either unprotected or only poorly protected by ribosomes, and therefore highly sensitive to endonucleolytic attack, and the other ribosome-bound with a half-life within the same range as that of sacB and csn transcripts.…”
Section: Discussionmentioning
confidence: 96%
“…It has been noted that the expression of proteins can be controlled by codon usage according to the cellular levels of tRNA, which fluctuate with growth conditions and growth phase (Saier, 1995 ;Shields & Sharp, 1987 ;Karlin & Mrazek, 2000). However, the different gene fusions constructed were all expressed under the same growth conditions and during the same growth phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several hypotheses have been made to explain the frequent association of ECDNA regions with tDNA loci (Cheetham & Katz, 1995;Hou, 1999;Reiter et al, 1989;Saier, 1995;Williams, 2002), it is still unclear why certain tDNAs are preferred ECDNA insertion sites. We can suggest several reasons why a tDNA is not an ECDNA insertion site, although none of them can fully explain our results.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous observations suggest that transfer RNA, although primarily involved in amino acid activation, may also control gene expression at different levels (reviewed in Söll, 1993)+ For instance, bacterial development can be regulated by low-abundance tRNA isoacceptors that modulate the expression of genes containing matching rare codons (Saier, 1995)+ Proteolytic degradation of several polypeptides can be triggered by a tRNA-dependent posttranslational addition of amino acids to the amino terminal residues of the protein+ This represents another example of the physiological versatility of the tRNA (Varshavsky, 1996)+ Regulation of the expression of specific tRNAs has been reported in response to cellular differentiation and growing conditions (reviewed in Sprague, 1995)+ However, different pathological conditions have also been associated with changes in tRNA metabolism+ Although point mutations in mitochondrial tRNA genes have been linked to numerous neuromuscular diseases (Graeber & Muller, 1998), variations in tRNA modifications (Dirheimer et al+, 1995) or tRNA expression (Mukerjee & Goldfeder, 1976;White, 1997) are often found in conjunction with neoplastic cell proliferation+…”
Section: Introductionmentioning
confidence: 99%